Case report: An adolescent female with anosmic hypogonadotropic hypogonadism, intellectual disability, and papillary thyroid carcinoma: heterozygous deletion of TCF12 - Celik, Nur Berna; Sezer, Abdullah; Genel, Nebiyye; Savas-Erdeve, Senay; Karaman, İbrahim; Cetinkaya, Semra (Frontiers in Endocrinology, 2024)
There is a growing list of molecular defects that are associated with hypogonadotropic hypogonadism (HH). TCF12, a recently identified molecular defect, causes craniosynostosis and is suggested to be used as a biomarker for prognosis in various cancer types. Recently, TCF12 variants were shown in a cohort with HH.Case Presentation: A 15.3 years old female patient was referred to the endocrinology clinic for obesity. She had been gaining weight from mid-childhood. She had her first epileptic seizure at the age of 15.1 years and mildly elevated thyroid autoantibodies were detected during evaluation for etiology of seizures. She had not experienced menarche yet. She was operated for left strabismus at the age of 7 years. School performance was poor and she was receiving special education. Tanner stage of breast was 1 and pubic hair was 3. The endocrine workup revealed hypogonadotropic hypogonadism. Also, the Sniffin' Sticks test detected anosmia. Thyroid ultrasonography was performed due to the mildly elevated thyroid autoantibodies, and thyroid nodules with punctate calcifications were detected. Total thyroidectomy and central lymph node dissection were performed regarding the cytological findings of the nodules and multicentric papillary thyroid carcinoma with no lymph node metastasis was detected on pathology specimens. Regarding the phenotypic features of the patients, whole exome sequencing was performed and heterozygous deletion of exon 1 and exon 6-8 in TCF12 was detected.Haploinsufficiency of TCF12 causes anosmic HH. Probably due to the incomplete penetrance and variable expressivity of the disease, patients could display variable phenotypic features such as intellectual disability, developmental delay, and craniosynostosis. Further description of new cases with TCF12 variations could enhance our understanding of craniosynostosis and its potential link to Kallmann syndrome associated with this gene..